Research on Performance of Chaotic Pulse Position Modulation Photon Counting LiDAR System - JIA Yihan; ZHANG Xuanwei; WANG Bingjie; XU Hang; LIU Li; LI Jingxia (Guangtongxin yanjiu)
【Objective】Photon counting LiDAR offers significant advantages in detecting long-range and weak targets due to its exceptionally high detection sensitivity. However, conventional photon counting LiDAR, which is based on periodic pulse signals, suffers from range ambiguity and is highly susceptible to interference from other LiDAR signals. As a result, it often leads to false alarms and misjudgments.【Methods】This paper presents a LiDAR system utilizing Chaotic Pulse Position Modulation (CPPM) and Time-Correlated Single Photon Counting (TCSPC) technology. A CPPM signal generator is designed using a Field Programmable Gate Array (FPGA) to directly modulate the laser and generate optical-domain chaotic pulse signals. Additionally, a time-correlated single photon counting system is constructed using a single photon detector and a Time to Digital Converter (TDC).【Results】Indoor ranging and 3-Dimensional (3D) imaging experiments are performed, and the ranging performance and anti-interference ability are tested experimentally.【Conclusion】The experimental results show that the photon-counting lidar system constructed in this paper, which uses a non-periodic pulse sequence generated by the CPPM method as the detection signal, does not have the problem of range ambiguity. Moreover, it can effectively suppress the cross-interference of traditional periodic pulse lidar signals at extremely low detection power.